Preparation and characterization of light-cured methacrylate/montmorillonite nanocomposites - Mucci, Veronica Lujan (2010)
Polymer/clay nanocomposites were prepared from dimethacrylate monomers, commonly used in dental restorative resins, and an organically modified silicate (montmorillonite). The photopolymerization process was hardly affected by the presence of the silicate filler, and thus 2 mm thick samples containing 3 wt% clay were extensively cured. Transmission electron microscopy revealed that the montmorillonite platelets were either intercalated or exfoliated. Nevertheless, for all formulations, intermediate-sized aggregates of about 1 µm were present and their fraction increased as the amount of filler increased. The presence of the clay was found to have no major effect on the flexural modulus and compressive yield strength of the nanocomposites. Moreover, the water uptake of nanocomposites containing 3 wt% clay was about 10–15% higher than that of unfilled monomers. Modification of the clay surface with alternative organic cations is certainly necessary in order to achieve an optimal dispersion of the clay in the polymer matrix.